2019
DOI: 10.1177/2040622319878997
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of obesity and overweight, associated demographic and lifestyle factors, and health status in the adult population of Jeddah, Saudi Arabia

Abstract: Background: Obesity is a risk factor for many chronic diseases, and its prevalence and trends vary among populations. Saudi Arabia shows a greater rise in prevalence than many other countries. We aimed to study the association between several chronic disorders, demographic, and lifestyle factors with increased body mass index (BMI) in the adult population of Jeddah. Methods: Data were obtained from a door-to-door cross sectional study. A three-stage stratified cluster sampling technique was adopted. Individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
1
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 31 publications
6
64
1
4
Order By: Relevance
“…In addition, several previous regional cross-sectional studies have indicated variations in obesity prevalence in the Kingdom [21,24,25]. Although these rates varied between regions due to limited sample size and differences in age groups, their ndings consistently align with our ndings on the higher obesity prevalence among women.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, several previous regional cross-sectional studies have indicated variations in obesity prevalence in the Kingdom [21,24,25]. Although these rates varied between regions due to limited sample size and differences in age groups, their ndings consistently align with our ndings on the higher obesity prevalence among women.…”
Section: Discussionsupporting
confidence: 89%
“…According to the framework, the basic causes including poverty, social condition, and political, economic, ecological, and other factors were the root reason for any form of malnutrition [13]. Different literature studies explicitly identified sociodemographic factors that were highly correlated with obesity, for example, older age [2,6], married (marital status) [14], low wealth index [6,10,[15][16][17], urban residency [6,10,16,18], being female [2,9], learning in private schools [2,9,19,20], easy accessibility of junk and fired or energy-dense foods and packed animal source foods due to free trade policy [2], rural to urban migration, replacement of local agribusiness with food retail [21], higher education level [6,7,22], and being pregnant [6,18]. In contrary to the previous findings, a study conducted among French women shows that having a higher income, a higher occupational class, and a higher educational level and having hot water at home reduce the occurrence of obesity [23] although the pathophysiology of hot water at home and obesity occurrence was not yet studied.…”
Section: Sociodemographic Factors Based On United Nationsmentioning
confidence: 99%
“…e prevalence of obesity among reproductive-age women was 5.1% in India [6], 15.7% in Palestinian schoolchildren, and 34.8% among adult populations of Saudi Arabia [7]. e prevalence of overweight and obesity was 40.9% in Kuwait among children aged 6-8 years.…”
Section: Introductionmentioning
confidence: 97%
“…The prevalence rate of obesity is on uttermost in Anglosphere countries inclusive USA, and Middle East high-income countries, which encompass severely obese patients [6,7]. Particularly, in Saudi Arabia the prevalence rate of obesity has been estimated to be 35.4% which is higher than its other neighboring countries 31.7% in United Arab Emirates, and 27% in Oman respectively [8]. A sedentary lifestyle is considered as one of its main reasons across the globe which is estimated at approximately 10% of the population is obese and approximately twice and thrice of 1970s data the reason behind this intake of the calories has increased across the world [9].…”
Section: Highlightsmentioning
confidence: 99%